Penegakan Hukum Pidana Terhadap Perusakan Kelestarian Lingkungan Tempat Wisata Oleh Wisatawan (Studi Penelitian Wisata Botu Motoli’ouwo) - Abdullatif, Nirma; Puluhulawa, Moh. Rusdyanto U.; Puluhulawa, Jufryanto (CV. ITTC INDONESIA, 2023)
Enforcement of criminal law against tourists who damage the environment in tourist attractions. The purpose of this research is to make the reader aware that acts damaging the environment, one of which is a tourist spot, can be subject to criminal sanctions in accordance with Law no. 10 of 2009 in the field of tourism. Using empirical research methods, this research study was carried out at the Botu Motoli'ouwa tourist spot, precisely in the province of Gorontalo. The results of this study explain the supervision of threats to pollution and environmental destruction of Botu Motoli'ouwo tourism objects, law enforcement and criminal liability for tourists who damage the sustainability of the tourism environment.